Comparative solvent evaluation for protein extraction from Channa striata and development of a stable capsule formulation for nutritional supplementation - Prayoga Drajat Pangestu Salim; Dewi Damayanti Abdul Karim; Syaikhul Aziz (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2025)
Background: Channa striata is a protein-rich freshwater fish with therapeutic potential, yet systematic optimization of extraction methods and stable formulation development remain limited. Objective: To compare protein extraction efficiency using three solvents (1% HCl, 0.9% NaCl, and distilled water) and develop optimized capsule formulations. Methods: Protein was extracted at 1:4 (w/v) ratio and quantified using the Lowry method at 595 nm. The method was verified for linearity (R = 0.998), accuracy (98-102%), and precision (RSD <2%). Extracts were formulated into capsules at 0, 300, 400, and 500 mg (F0-F3) and evaluated for quality parameters and 28-day stability at -4°C, 24°C, and 40°C. Data were analyzed using one-way ANOVA with Duncan's post-hoc test. Results: The 1% HCl yielded highest protein content (4.947 ± 0.071 mg/mL) and extraction efficiency (21.390%) compared to 0.9% NaCl and distilled water (p <0.05). All formulations met pharmaceutical standards. Notably, F3 maintained protein retention >95% across all storage conditions (97.1-99.3%), while F0-F2 failed this criterion. Conclusion: The 1% HCl demonstrated optimal extraction efficiency. F3 (500 mg) exhibited superior stability and dissolution characteristics, representing a promising candidate for C. striata-based nutritional supplements.